Light-driven Uptake of Oxygen, Carbon Dioxide, and Bicarbonate by the Green Alga Scenedesmus - Radmer, Richard (1980)
Mass spectrometric techniques were used to study several aspects of the competition between O(2) and species of inorganic carbon for photosynthetically generated reducing power in the green alga, Scenedesmus. In contrast to wild type, no appreciable light-driven O(2) uptake was observed in a mutant lacking photosystem I. It is concluded that the carbon cycle-independent reduction of O(2) occurs at the expense of photosystem I-generated reducing equivalents. The commonly observed differences between CO(2)-grown and air-grown Scenedesmus with respect to CO(2) uptake and glycolate formation cannot be ascribed to differences in their capacity for light-driven O(2) uptake. There were no intrinsic differences found in O(2) uptake capacity between the two physiological types under conditions in which CO(2) was saturating or CO(2) uptake was inhibited. It was only under CO(2)-limited conditions that pronounced differences between the two physiological types were observed. This fact suggests that differences in O(2) metabolism and sensitivity between the two types really reflect differences in their capacity to assimilate inorganic carbon; in this respect they are analogous to C(3) and C(4) plants. The hypothesis that air-grown Scenedesmus can assimilate HCO(3)(−) by directly monitoring the time course of dissolved CO(2), O(2) uptake, and O(2) evolution in illuminated algal suspensions at alkaline pH was tested. Inasmuch as the measuring technique employed was fast compared to the nonenzymic equilibration of the inorganic carbon species, it was possible to determine the degree to which the CO(2) concentration deviated from equilibrium (with the other inorganic carbon species) during the course of illumination. The observed kinetics in air-grown and CO(2)-grown algae in the presence and absence of carbonic anhydrase, and a comparison of these kinetics with theoretical (computer-generated) time courses, support the idea that air-adapted algae are able to assimilate HCO(3)(−) actively at a high rate. The data suggest that these algae preferentially assimilate CO(2) and supply the balance of their needs by taking up HCO(3)(−). Since (unlike C(4) plants) these algae have no special CO(2) pump, and thus have a relatively low affinity for CO(2), HCO(3)(−) assimilation is the major carbon uptake process at alkaline pH even when the total CO(2) is present in millimolar concentrations.